Knowledge and Treatment Adherence as Determinants in the Control of HIV/AIDS: A Social Epidemiology Approach - Kusdiyah, Erny; aurora, Wahyu Indah Dewi; Syauqy, Ahmad; Miftahurrahmah, Miftahurrahmah; Wulandari, Putri Sari; Maria, Ima; Darmawan, Armaidi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: HIV/AIDS remains a major public health challenge worldwide, and treatment adherence continues to be a critical factor in achieving effective viral suppression. Knowledge about HIV prevention plays a vital role in shaping health behaviors and promoting adherence to antiretroviral therapy (ART). This study aimed to analyze the association between knowledge of HIV prevention and treatment adherence among people living with HIV/AIDS (PLWHA) using a social epidemiology framework. Methods: A cross-sectional quantitative study was conducted among 101 PLWHA receiving ART in public health centers and clinics. Data were collected through structured questionnaires covering demographic characteristics, knowledge of HIV prevention, and treatment adherence, verified with medical records. Data were analyzed using descriptive statistics and the Chi-square test (α = .05) to assess the relationship between knowledge and adherence levels. Results: The majority of respondents were male (82.2%) and had completed secondary education (66.3%). Most participants demonstrated fair to good levels of HIV prevention knowledge; however, adherence levels varied. The Chi-square test revealed a highly significant association between knowledge and treatment adherence, χ²(4) = 202, p < .001, indicating that higher knowledge was strongly correlated with improved adherence. Conclusion: The findings emphasize that knowledge enhancement significantly improves ART adherence and contributes to the control of HIV/AIDS. Strengthening education programs, peer support, and community engagement are essential strategies to foster sustainable adherence and align national efforts with global HIV prevention targets.